High Temperature Corrosion of Nickel in NaVO3-V2O5 Melts - J. Porcayo-Calderon; J. J. Ramos-Hernandez; Jan Mayén; E. Porcayo-Palafox; G. K. Pedraza-Basulto; J. G. Gonzalez-Rodriguez; L. Martinez-Gomez (Advances in Materials Science and Engineering)
Many alloys used at high temperature in industrial processes are Ni-based and many others contain it in appreciable quantities, so it is of interest to evaluate the performance of pure nickel in order to determine the behavior of its alloys once the elements responsible for their protection have been depleted due to accelerated corrosion processes in the presence of vanadium-rich molten salts. Due to this, this work presents the study of Ni behavior in NaVO3-V2O5 mixtures at different temperatures. The behavior of pure nickel was determined by both electrochemical and mass loss measurements. The results show that the aggressiveness of the vanadium salts is increased by increasing both the V2O5 content and temperature. V2O5 addition considerably increases the current densities of the anodic and cathodic reactions. The corrosion process of Ni is modified due to the presence of its corrosion products, and its presence increases the activation energy by at least one order of magnitude. Although nickel shows a high reactivity in vanadium-rich salts, its reaction products are highly stable and protect it from the corrosive medium because the corrosion reactions trap the vanadium and block the migration of nickel ions.